New strontium-based coatings show activity against pathogenic bacteria in spine infection - Ghezzi, Daniele; Graziani, Gabriela; Cappelletti, Martina; Fadeeva, Inna V.; Montesissa, Matteo; Sassoni, Enrico; Borciani, Giorgia; Barbaro, Katia; Boi, Marco; Baldini, Nicola; Rau, Julietta V. (Frontiers in Bioengineering and Biotechnology, 2024)
Infections of implants and prostheses represent relevant complications associated with the implantation of biomedical devices in spine surgery. Indeed, due to the length of the surgical procedures and the need to implant invasive devices, infections have high incidence, interfere with osseointegration, and are becoming increasingly difficult to threat with common therapies due to the acquisition of antibiotic resistance genes by pathogenic bacteria. The application of metal-substituted tricalcium phosphate coatings onto the biomedical devices is a promising strategy to simultaneously prevent bacterial infections and promote osseointegration/osseoinduction. Strontium-substituted tricalcium phosphate (Sr-TCP) is known to be an encouraging formulation with osseoinductive properties, but its antimicrobial potential is still unexplored. To this end, novel Sr-TCP coatings were manufactured by Ionized Jet Deposition (IJD) technology and characterized for their physiochemical and morphological properties, cytotoxicity, and bioactivity against Escherichia coli ATCC 8739 and Staphylococcus aureus ATCC 6538P human pathogenic strains. The coatings are nanostructured, as they are composed by aggregates with diameters from 90 nm up to 1 µm, and their morphology depends significantly on the deposition time. The Sr-TCP coatings did not exhibit any cytotoxic effects on human cell lines and provided an inhibitory effect on the planktonic growth of E. coli and S. aureus strains after 8 hours of incubation. Furthermore, bacterial adhesion (after 4 h of exposure) and biofilm formation (after 24 h of cell growth) were significantly reduced when the strains were cultured on Sr-TCP compared to TCP only coatings. On Sr-TCP coatings, E. coli and S. aureus cells were not organized in a biofilm-like structure and showed morphological alterations due to the toxic effect of the metal. These results demonstrate the stability and anti-adhesion/antibiofilm properties of IJD-manufactured Sr-TCP coatings, which represent potential candidates for future applications to prevent prostheses infections and to promote osteointegration/osteoinduction.